The Effects of Urbanization on Indonesian Community and Environment - Noviani, Rita; Saputra, Aditya Eka; Rochmatullah, Mahameru Rosy (Faculty of Geography, Universitas Gadjah Mada, 2025)
This research aims to analyze the impact of urbanization on environmental and socio-economic resilience of communities by investigating the Sukoharjo region in Indonesia. Several components of urban ecosystem were considered, including geological formations, geomorphological conditions, and eco-regions. Meanwhile, the analysis of urban socio-economic aspects focuses on community well-being and urban facilities. The research uses 180 observation samples in the analysis process. The result shows that urbanization deteriorates soil fertility, agricultural land, and the availability of clean water through panel data regression. In addition, urbanization has successfully increased per capita income, employment opportunities, and the development of public facilities, posing a dilemma for policymakers. This shift in population needs to be pursued by some communities to preserve urban ecosystem. Urbanization has a positive and negative impact on community welfare and ecosystems, respectively. In this context, future research must adopt effective methods for managing urbanization and urban ecosystems.Received: 2023-10-26 Revised: 2024-01-25 Accepted: 2025-02-19 Published: 2025-03-25